Agricultural robotics: part of the new deal? FIRA 2020 conclusions - Lenain, Roland (éditions Quae, 2021)
Throughout the fifth edition of the International Forum of Agricultural Robots (FIRA) in December 2020, more than 1,500 farmers, manufacturers, advanced technology suppliers, innovators, investors, journalists and experts from 71 countries around the world gathered to ask questions, share stories and exchange ideas about agricultural robots. This book is a journey into the state of the art of this industry in 2020, and includes 27 agricultural robot information sheets. It is designed to provide a nuanced look at the industry's most pressing topics, from the overarching impact of the global food crisis to the everyday influence of semi-autonomous tractors on a family-owned farm in France. The book achieves this goal by taking a deep dive into the perspectives shared by FIRA 2020 presenters and panelists.